Nurses' perceptions to alleviate dyspnoea in inpatients with advanced cancer while receiving palliative care - Johanna Kero; Jaana‐Maija Koivisto; Siew Hwa Lee; Elina Haavisto (Wiley, 2024)
Abstract Aim To explore nurses' perceptions to alleviate dyspnoea in inpatients with advanced cancer while receiving palliative care. Design A descriptive qualitative design. Methods Seven focus groups were conducted with nurses (n = 27) from five specialized palliative care wards in four hospitals in south and southwest Finland. The focus groups were conducted between June and November 2019, and the transcripts were analysed using inductive analysis. Results The findings revealed three categories: recognizing dyspnoea is a multi‐faceted problem, dealing with the complexity of assessment of dyspnoea and strategies for relieving dyspnoea. Nurses perceived the complexity of dyspnoea as a symptom and emphasized the importance of utilizing patients' subjective experiences and consistent assessment scales to determine its severity. Furthermore, nonpharmacological interventions are as pertinent as pharmacological and medical interventions. The findings can assist nurses in selecting appropriate interventions for dyspnoea care, ultimately enhancing the quality of patient care and patient safety.